Feasibility of Ecological Momentary Assessment Using Cellular Telephones in Methamphetamine Dependent Subjects - Gantt P. Galloway; Ryne Didier; Kathleen Garrison; John Mendelson (SAGE Publishing, 2008)
Background Predictors of relapse to methamphetamine use are poorly understood. State variables may play an important role in relapse, but they have been difficult to measure at frequent intervals in outpatients. Methods We conducted a feasibility study of the use of cellular telephones to collect state variable data from outpatients. Six subjects in treatment for methamphetamine dependence were called three times per weekday for approximately seven weeks. Seven questionnaires were administered that assessed craving, stress, affect and current type of location and social environment. Results 395/606 (65%) of calls attempted were completed. The mean time to complete each call was 4.9 (s.d. 1.8) minutes and the mean time to complete each item was 8.4 (s.d. 4.8) seconds. Subjects rated the acceptability of the procedures as good. All six cellular phones and battery chargers were returned undamaged. Conclusion Cellular telephones are a feasible method for collecting state data from methamphetamine dependent outpatients.